Eukaryotic rather than prokaryotic microbiomes change over seasons in rewetted fen peatlands. Issue 9 (24th August 2021) - Wang, Haitao; Weil, Micha; Dumack, Kenneth; Zak, Dominik; Münch, Diana; Günther, Anke; Jurasinski, Gerald; Blume-Werry, Gesche; Kreyling, Jürgen; Urich, Tim
ABSTRACT: In the last decades, rewetting of drained peatlands is on the rise worldwide, to restore their significant carbon sink function. Despite the increasing understanding of peat microbiomes, little is known about the seasonal dynamics and network interactions of the microbial communities in these ecosystems, especially in rewetted fens (groundwater-fed peatlands). Here, we investigated the seasonal dynamics in both prokaryotic and eukaryotic microbiomes in three common fen types in Northern Germany. The eukaryotic microbiomes, including fungi, protists and microbial metazoa, showed significant changes in their community structures across the seasons in contrast to largely unaffected prokaryotic microbiomes. Furthermore, our results proved that the dynamics in eukaryotic microbiomes in the rewetted sites differed between fen types, specifically in terms of saprotrophs, arbuscular mycorrhiza and grazers of bacteria. The co-occurrence networks also exhibited strong seasonal dynamics that differed between rewetted and drained sites, and the correlations involving protists and prokaryotes were the major contributors to these dynamics. Our study provides the insight that microbial eukaryotes mainly define the seasonal dynamics of microbiomes in rewetted fen peatlands. Accordingly, future research should unravel the importance of eukaryotes for biogeochemical processes, especially the under-characterized protists and metazoa, in these poorly understood ecosystems. Abstract : Eukaryotes, especially of under-characterized protists and microbial metazoa, are important in understanding the dynamics of soil food webs and ecosystem functionality of fen peatlands.